Treatment of radius, ulna and humerus fractures with the aid of a bone morphogenetic protein in a giant anteater (Myrmecophaga tridactyla) - Ferrigno, CRA; Futema, F.; Fedullo, D. L.; Kyan, V; Fantoni, D. T.; Baccarin, DCB; Romano, M. A. (Schattauer Gmbh-verlag Medizin Naturwissenschaften, 2003)
A giant anteater (Myrmecophaga tridactyla) was found with closed comminuted fractures on the fight radius and ulna and left humerus he duration of which was unknown. The animal was unable to use either of he thoracic limbs. The fractures were stabilized with 3.5-mm titanium plates and a commercially available mixture of micro lyophilized bovine cortical osseous and bovine BMP (Gen-tech(R), Baumer, Brazil) was implanted into the fractures sites. Postoperative radiographic evaluations were performed every 30 days and after four months. Bone healing was observed in all of he fractures. The animal was able to be reintroduced into its natural habitat. From his case we conclude that despite he low metabolic fate of the giant anteater, which is an inherent characteristic of this species, he treatment of radius, ulna and humerus fractures by means of plates and screws, associated with BMP on the Myrmecophaga tridactyla, was a success.
Keywords: anteater; BMP; fracture